2014
DOI: 10.1007/s00428-014-1616-4
|View full text |Cite
|
Sign up to set email alerts
|

SPARC/osteonectin is involved in metastatic process to the lung during melanoma progression

Abstract: The existence of a "metastasis gene signature" that predisposes primary breast cancer cells to metastasize to the lungs has been recently highlighted by gene expression profiling studies. The combination of genes responsible for this process includes genes encoding several metalloproteinases as well as the gene encoding SPARC (secreted protein acidic and rich in cysteine)/osteonectin. SPARC is involved in normal tissue remodeling as it regulates the deposition of extracellular matrix, but also plays a role in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Clinically, our findings are underlined by the high expression of SPARC that we observed in pulmonary metastases of melanoma biopsies. Interestingly, a recent study found SPARC overexpressed mainly in lung metastases from melanoma as compared with other primary tumours 46 .…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, our findings are underlined by the high expression of SPARC that we observed in pulmonary metastases of melanoma biopsies. Interestingly, a recent study found SPARC overexpressed mainly in lung metastases from melanoma as compared with other primary tumours 46 .…”
Section: Discussionmentioning
confidence: 99%
“…All these results suggest that IGTA1, VCAM1, SPARAC and ANGPTL4 could be the drivers of HCC metastatic tropisms. Although, the gains-of-functions or/and loss-of-functions of these candidates need be further explored [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, we note there are certain cases where MCP expression has been shown to oppose cancer development (51,52). SPARC protein is highly expressed in cancer cells and the stroma of certain cancers, including glioma, breast and cervical melanoma (53)(54)(55)(56), where it exhibits oncogenic roles in cell growth, invasion and apoptosis. Interestingly, SPARC has also been associated with tumor suppression by influencing these same processes (57).…”
Section: Expression Of Mcps In Cancermentioning
confidence: 90%